KARAKTERISTIK DAN KUALITAS MUTU KARAGINAN RUMPUT LAUT DI INDONESIA - Surya Adi Saputra; Muammar Yulian; Khairun Nisah (UIN AR-RANIRY, 2021)
Carrageenan is a product produced from the extraction process of red seaweed (Rhodophyceae). Carrageenan can be used in various business fields, both in the food and non-food sectors, which function as a gelling additive, binder, emulsifier and stabilizer. The research method used is Literature Review with data collection and screening that has inclusion and exclusion criteria. The results obtained indicate that the quality characteristics and quality for water content and average gel strength have not met the established standards, while the yield value, ash content and average viscosity have met the quality standards set by FAO, FCC and EEC. . The factors that greatly affect the characteristics and quality of carrageenan from seaweed are alkaline concentration, seaweed harvesting age, temperature and extraction time as well as the type and environmental conditions where the seaweed grows.